Nanofiltration membranes for salt and dye filtration effect of membrane properties on performances - Ağtaş, Meltem (Water science and technology : a journal of the International Association on Water Pollution Research, 2021)
In this study, commercial nanofiltration membranes (Toray, NF 270, Desal 5 L) were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, optical profilometry, contact angle, mechanical strength and zeta potential measurements. Filtration performance tests were conducted with distilled water, MgSO4 solution and synthetic dye solutions, respectively. Among three commercial membranes, the Toray membrane was thought to be better choice. Additional experiments were carried out for a more detailed characterization of the selected membrane. Therefore, firstly, flux and removal efficiency was monitored by using dye solutions at different pH values, and then experiments were carried out to observe the effect of different temperatures. Also, another filtration test with NaCl solution was performed for the Toray membrane. As the main purpose of this study, we aimed to establish a significant correlation between the structural properties of membranes and their performances. In light of the results obtained, it was observed that the contact angle, mechanical strength and surface roughness values of the membrane significantly affected the membrane performance. It was concluded that the most important parameter in dye removal was the zeta potential. As a result of this work, a data set of commercial membranes was created and is available to all membrane users